KEANEKARAGAMAN JENIS MAMALIA DI ARBORETUM UNIVERSITAS RIAU KOTA PEKANBARU PROVINSI RIAU - Dwi Seprina; Defri Yoza; Evi Sribudiani (Fakultas Pertanian, Universitas Riau, 2018)
Arboretum of Riau University is a habitat whom build a one connection potential habitat for wildlife and more organism. As a supporting tool that provides useful information for various purposes, booth in terms of education, social, economic and ecology. It is necessary to support the complete data by conducting research on the animals in the Arboretum of Riau University, especially mamals, to find out the large index of diversity and richness of mammals species contained in Arboretum of Riau University. This Research held on November 2016 until Januari 2017. Method used for this research is a line transects method and trap. On research location obtained result is there 9 of mammals from 6 family founded with 63 individu that founded. The indeks of species diversity in both dry line (1,93) and wet line (1,73) was moderate. Richness indeks good varieties dry line (1,97) wet line (1,80) is low. Most of mammals on Arboretum of Riau University are animals living on forest floor (teresterial), small flying mammals are met for while research only bats and kind of living animals on canopy area crown and the middle of the canopy crown (arboreal).